Eksplorasi Kecerdasan Ganda Pada Siswa Kelas 5 dan 6 di MI Al Wardah Pamulang - Rahma Adzkia (Pendidikan Al-Gafari, 2025)
This research analyzes students' multiple intelligences through a questionnaire. The results showed that students were more confident in linguistic abilities compared to artistic and physical activities. The T-test showed there were no significant differences between the groups tested. Apart from that, the influence of extracurricular activities and students' daily activities is very influential in shaping their preferences and abilities. These findings provide insight into student preferences that can aid the development of more effective and inclusive teaching methods, and underscore the importance of supporting extracurricular activities in the development of students' multiple intelligences. Therefore, understanding the role of a holistic learning environment can increase students' potential intelligence in various fields. This research also identified that family and teacher support in extracurricular activities contributed significantly to increasing students' self-confidence and independence. Apart from that, the results of this research can be a consideration in making educational policies that are more responsive to the various needs and potential of students. This study illustrates the importance of integrating the concept of multiple intelligences in the existing school curriculum, with an emphasis on a more personalized and adaptive learning approach. In this way, it is hoped that students can develop various aspects of their intelligence optimally, so that they become more competitive and insightful individuals in the future.